Jean Gayon and the French School of Population Genetics - (:unkn) unknown (My University, 2023)
Background and objectives—Podocarpus latifolius (synonym of P. milanjianus) is a key tree representative of Afromontane forests where it is highly threatened by climate and land-use changes. While large populations occur in East Africa, only a few isolated and usually small populations remain in western Central Africa (Cameroon to Angola). Studying the evolutionary history of such relictual populations can thus be relevant to understand their resilience under changing environments. Materials and Methods—we developed nine polymorphic nuclear microsatellites (nSSRs) to estimate genetic variability, (historical) gene flow, and demographic changes among natural populations from Central to East Africa. Results—despite the extended distribution range of P. latifolius, a strong isolation-by-distance pattern emerges at the intra-population scale, indicating low seed and pollen dispersal capacities. Central African populations display a lower genetic diversity (He = 0.34 to 0.61) and are more differentiated from each other (FST = 0.28) than are East African populations (He = 0.65 to 0.71; FST = 0.10), suggesting high genetic drift in the Central African populations. Spatial genetic structure reveals past connections between East and West Africa but also a gene flow barrier across the equator in western Central Africa. Demographic modelling anchors the history of current lineages in the Pleistocene and supports a strong demographic decline in most western populations during the last glacial period. By contrast, no signature of demographic change was detected in East African populations. Conclusions—in Cameroon, our results exclude a recent (re)colonization from one source population of all mountain ranges, but rather indicate long-term persistence of populations in each mountain with fluctuating sizes. A higher impact of genetic drift and further loss of diversity can be expected by survival through climatically unfavorable periods in such small refugial
Keywords: African Research